The characteristics of chemistry test items on nationally-standardized school examination in Yogyakarta City - Ummul Karimah; Heri Retnawati; Deni Hadiana; Pujiastuti Pujiastuti; Eri Yusron (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2021)
This study aimed to describe the characteristics of chemistry test items in Nationally Standardized School Examination or Ujian Sekolah Berstandar Nasional (USBN), consisted of discrimination index, difficulty index, and question reliability. The data were collected by using documentation of the answers of 194 students. The type of research was descriptive exploratory with quantitative and qualitative approaches. Quantitative data analysis was performed by using the classical test theory approach and item response theory with 1 logistical parameter. Meanwhile, qualitative data analysis was conducted to describe the items categorized as difficult and bad categories. The results show that, according to classical test theory, the USBN Chemistry item test has an average level of difficulty of 0.57, which is categorized as moderate. Regarding the discrimination index, the average of different test power obtained is equal to 0.146 and belongs to the good category. Based on the item response theory, the average difficulty index of -0.00086 is categorized as moderate. The results of the estimated reliability of the questions amounted to 0.48 is included in the moderate category. The results of the qualitative analysis show that the items which belong to the difficult category are the items on salt hydrolysis material, acid-base titration, the concept of periodicity, manufacture, and use of chemical compounds according to classical test theory. Meanwhile, according to the theory of response, items that belong to the difficult category were found in acid-base titration material, the colligative solution phenomenon, and the concept of periodicity of the main metal elements.